A novel pH-sensitive carrier for the delivery of antitumor drugs: histidine-modified auricularia auricular polysaccharide nano-micelles - Yingying Wang (Nature Portfolio, 2017)
Abstract The study was aimed to design a novel pH-sensitive carrier to deliver antitumor drugs to increase treatment efficiency. Histidine (His)was used to modify auricularia auricular polysaccharide (AAP) by esterification. Proton nuclear magnetic resonance spectrometry was developed to characterize the His-AAP carrier and the His-AAP Paclitaxel (PTX) micelles were prepared by self-assembled organic solvent evaporation. The formation of His-AAP PTX micelles was confirmed by dynamic light-scattering, transmission electron microscopy and high performance liquid chromatography. It was found that the His-AAP PTX micelles possessed a spherical morphology with an average diameter of 157.2 nm and an 80.3% PTX encapsulation efficiency. In vitro release at pH 7.4, 6.5, 5.0 reached 70%, 71%, and 88%, respectively. The cell viability assay and confocal laser scanning microscope were used to evaluate the cytotoxicity and cell uptake of the His-AAP PTX micelles. Compared with Taxol, the IC50 of the His-AAP PTX micelles were lower after incubating for 24 h, 48 h, or 72 h (0.216 versus 0.199, 0.065 versus 0.060, and 0.023 versus 0.005, respectively). In a test of tumor-bearing mice, the His-AAP PTX micelles significantly inhibited tumor growth. These results showed that His-AAP PTX micelles are a highly promising therapeutic system for anticancer therapy.